2021
DOI: 10.1371/journal.pone.0260312
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic effect of co-administration of furosemide and albumin in comparison to furosemide therapy alone: An updated systematic review and meta-analysis

Abstract: Background It has been a matter of much debate whether the co-administration of furosemide and albumin can achieve better diuresis and natriuresis than furosemide treatment alone. There is inconsistency in published trials regarding the effect of this combination therapy. We, therefore, conducted this meta-analysis to explore the efficacy of furosemide and albumin co-administration and the factors potentially influencing the diuretic effect of such co-administration. Methods In accordance with the Preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 29 publications
1
38
1
2
Order By: Relevance
“…The treatment effect was more pronounced in patients with serum albumin Fig. 1 Albumin therapy in critical care levels < 2.5 g/dl and higher prescribed albumin infusion doses (> 30 g), but the heterogeneity was high [9]. Importantly, the effect on urine output was more prominent in the first 12 h after co-administration.…”
Section: Myth #5 Albumin Improves the Effects Of Diureticsmentioning
confidence: 97%
“…The treatment effect was more pronounced in patients with serum albumin Fig. 1 Albumin therapy in critical care levels < 2.5 g/dl and higher prescribed albumin infusion doses (> 30 g), but the heterogeneity was high [9]. Importantly, the effect on urine output was more prominent in the first 12 h after co-administration.…”
Section: Myth #5 Albumin Improves the Effects Of Diureticsmentioning
confidence: 97%
“…A total of 12 (60%) patients had LVEF ≥50%. The median (p25-p75%) of IVC diameter was 22.5 mm (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Half of the patients displayed IVC diameter ≤21 mm.…”
Section: Resultsmentioning
confidence: 99%
“…To manage tissue congestion, different approaches aiming to facilitate the intravascular volume recruitment (transferring water from extravascular to an intravascular compartment) by increasing plasmatic osmolarity are used without robust evidence. These strategies included the infusion of loop diuretic together with a saline hypertonic solution or albumin (5,6,18,19). Another approach consists of using pharmacological agents such as SGLT2i or tolvaptan that increase urine-free water elimination (4,20).…”
Section: Diuretic Response: the Role Of Extravascular Congestion And ...mentioning
confidence: 99%
“…It is important to highlight the population and methods differences of these previous studies that might explain the results differences. A recent meta-analysis revealed that albumin co-administration increased urine output by 31.45 mL/h and urine sodium excretion by 1.76 mEq/h compared to furosemide alone (Lee et al, 2021). This effect was better in patients with low baseline serum albumin levels (<2.5 g/L) and high albumin infusion dose (>30 g) and within 12 h after administration.…”
Section: Intravenous Albuminmentioning
confidence: 99%